2019
DOI: 10.7554/elife.47682
|View full text |Cite
|
Sign up to set email alerts
|

The tardigrade damage suppressor protein binds to nucleosomes and protects DNA from hydroxyl radicals

Abstract: Tardigrades, also known as water bears, are animals that can survive extreme conditions. The tardigrade Ramazzottius varieornatus contains a unique nuclear protein termed Dsup, for damage suppressor, which can increase the resistance of human cells to DNA damage under conditions, such as ionizing radiation or hydrogen peroxide treatment, that generate hydroxyl radicals. Here we find that R. varieornatus Dsup is a nucleosome-binding protein that protects chromatin from hydroxyl radicals. Moreover, a Dsup orthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 45 publications
3
94
0
Order By: Relevance
“…In these cells, loss of HMGNs increased the extent of G2-M checkpoint arrest and apoptosis [64]. An additional possible link between DNA damage and HMGN proteins is shown by a recent finding that the damage repressor protein Dsup of tardigrade Ramazzottius varieornatus, which binds to DNA and protects from hydroxy free radicals, exhibits sequence similarity with HMGN proteins [65].…”
Section: Cancermentioning
confidence: 98%
“…In these cells, loss of HMGNs increased the extent of G2-M checkpoint arrest and apoptosis [64]. An additional possible link between DNA damage and HMGN proteins is shown by a recent finding that the damage repressor protein Dsup of tardigrade Ramazzottius varieornatus, which binds to DNA and protects from hydroxy free radicals, exhibits sequence similarity with HMGN proteins [65].…”
Section: Cancermentioning
confidence: 98%
“…Components of traditional DNA damage repair pathways have been found to be present in many tardigrade species, and a novel tardigrade protein, Dsup, has been identified that suppresses DNA damage (Hashimoto et al, 2016;Yoshida et al, 2017;Carrero et al, 2019;Kamilari et al, 2019). Dsup binds to DNA and prevents fragmentation in response to X-ray irradiation, H 2 O 2 , and hydroxyl radicals (Hashimoto et al, 2016;Hashimoto and Kunieda, 2017;Chavez et al, 2019). Expression of Dsup in cultured human cells can improve survival of X-ray irradiation and enable subsequent proliferation (Hashimoto et al, 2016).…”
Section: Dna Preservationmentioning
confidence: 99%
“…Importantly, tardigrades show an extraordinary tolerance towards extreme levels of radiation, a tolerance that has been directly linked to their anhydrobiotic capabilities 31 . It was recently shown that the tardigrade damage suppressor protein Dsup, which seemingly can protect human cells from radiation damage, binds to nucleosomes protecting chromosomal DNA from reactive hydroxyl radicals 29,32 . All tardigrades seem to have a comprehensive number of genes encoding proteins involved in antioxidant defense 30 .…”
mentioning
confidence: 99%